Keusahawanan Islam di kalangan mahasiswa Universiti Utara Malaysia Kedah - Muhammad Fahmi, Zulkifli (2016)
Entrepreneurship is a major contributor to the Malaysian economy. Efforts to introduce entrepreneurship programs in higher institutional level have done since 2007. It aims to encourage students or graduates to become entrepreneurs. This is because the country's economy towards an industrialized nation by the year 2020. In addition, entrepreneurial activity can prevent students from unemployed after they have graduated. Islamic entrepreneurship needs to be applied in the community, especially students because the majority of people in this country are Muslim moreover Islam is official religion in Malaysia. There are several factors that encourage students to venture into business at the university level. Accordingly, the aim of this study was to identify factors that influence North University of Malaysia (UUM) Kedah towards Islamic entrepreneurial venture. Studies performed on Muslim students of UUM. A total of 313 students have been involved with this study. This study used quantitative methods, the use of primary resources by distributing a questionnaire to the respondents to gather their data. The data were analyzed using Statistical Package for Social Science (SPSS version 22.0). Findings of the study found that attitude, idol, social, religious and entrepreneurship education has a positive relationship with the Islamic entrepreneurship. In conclusion, the results showed that students UUM agreed attitude, idol, social, religious and entrepreneurship education is contribute to the impact on their propensity for Islamic entrepreneurship.